(untitled) (Research, Society and Development, 2021)
The collared peccary (Pecari tajacu Linnaeus, 1758) is considered an animal of economic viability for trading and potentially productive for meat, being important the knowledge about the health of this species. Thus, the objective of the research was to carry out a cross-sectional study of leptospirosis in captive collared peccary (Pecari tajacu) from the states of Paraíba, Rio Grande do Norte and Piauí, northeast region of Brazil, using serological and molecular techniques. Serum samples from 48 animals were tested using the microscopic agglutination test (MAT) technique. In the samples of vaginal and preputial fluid, the Polymerase Chain Reaction (PCR) was performed. Four animals (8.3%) were seroreactive for Leptospira sp. with reaction to serogroup Icterohaemorraghiae and negative in PCR. There was association between the occurrence of leptospirosis and the intensive breeding system (odds ratio=63.00; 95%CI=4.3-910.6; P=0.002). The seroreactivity for leptospirosis suggests that, at some point, these animals were infected by sources of infection within the farm itself. It was also possible to observe the importance of knowing the serogroups prevalent in this species in the studied region, which allows the establishment of adequate strategies for its control, thus prioritizing the balance in the human-animal-environment relationship.